2021
DOI: 10.1371/journal.pone.0249406
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphisms affect miRNA target prediction in bovine

Abstract: Single nucleotide polymorphisms (SNPs) can have significant effects on phenotypic characteristics in cattle. MicroRNAs (miRNAs) are small, non-coding RNAs that act as post-transcriptional regulators by binding them to target mRNAs. In the present study, we scanned ~56 million SNPs against 1,064 bovine miRNA sequences and analyzed, in silico, their possible effects on target binding prediction, primary miRNA formation, association with QTL regions and the evolutionary conservation for each SNP locus. Following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 77 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…Duan et al (2003) reported that some synonymous mutations led to a decrease in mRNA stability and translation, and dramatically changed dopamine-induced upregulation of DRD2 expression. In addition, a study observed that the presence of SNPs can alter hairpin conformation due to loss or acquisition of base pairing, consequently altering free energy in primary miRNAs (Sousa et al, 2021). Also, the c.1470G>T mutation is predicted to change the mRNA secondary structure of BMPR1B.…”
Section: Discussionmentioning
confidence: 99%
“…Duan et al (2003) reported that some synonymous mutations led to a decrease in mRNA stability and translation, and dramatically changed dopamine-induced upregulation of DRD2 expression. In addition, a study observed that the presence of SNPs can alter hairpin conformation due to loss or acquisition of base pairing, consequently altering free energy in primary miRNAs (Sousa et al, 2021). Also, the c.1470G>T mutation is predicted to change the mRNA secondary structure of BMPR1B.…”
Section: Discussionmentioning
confidence: 99%
“…Water buffalo miRNAs and SNPs can be further used as genomic resources. Such use has been reported in cattle where SNPs and miRNAs have been found associated with bovine phenotypes to be used in breed improvement ( Sousa et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, two SNP in the 3 -UTR induce the deletion and/or the substitution of several miRNA binding sites. Some of these miRNA were associated with milk production traits including milk fat metabolism [72,73]. Therefore, the impact of the alteration/substitution of miRNA target sites from SNP in 3 -UTR of CSN1S2 would be interesting for investigations in an experimental study.…”
Section: Csn1s2mentioning
confidence: 99%